First Demonstration of a High‐Speed and High‐Power‐Tolerance InGaAs/Si Photodiode Fabricated by Atomic Diffusion Bonding. Issue 3 (29th September 2020) - Yamada, Yuki; Nada, Masahiro; Uomoto, Miyuki; Shimatsu, Takehito; Nakajima, Fumito; Matsuzaki, Hideaki
Abstract : A novel high‐speed photodiode (PD) with an InGaAs/Si structure fabricated by atomic‐diffusion bonding (ADB) is proposed with the aim of improving the heat transfer. The fabricated PD shows a responsivity of 0.42 A W −1 and a 3 dB bandwidth of over 50 GHz. The maximum damage‐threshold photocurrent, or high‐power tolerance, is higher than that of a conventional PD on an InP substrate, thanks to the high thermal conductivity of Si used as the collector in the PD. Abstract : A novel high‐speed photodiode (PD) with an InGaAs/Si structure fabricated by atomic‐diffusion bonding is proposed with the aim of improving the heat transfer. The fabricated PD exhibits a responsivity of 0.42 A W −1 and a 3 dB bandwidth of over 50 GHz. The maximum damage‐threshold photocurrent, or high‐power tolerance, is higher than that of a conventional PD on an InP substrate.